2018
DOI: 10.1002/pssa.201800250
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of High Temperature Annealing on the Photoluminescence of ZnMgO Alloys

Abstract: The effect of thermal annealing on the luminescence of wurtzite ZnMgO alloys in the films and ceramics produced by solid state reaction route is investigated. Formation of hexagonal ZnMgO phase is proved by X‐ray diffraction, micro‐Raman, photoluminescence (PL), and PL excitation methods. Mg starts incorporating into ZnO lattice at 700 °C, and its content increases with the increase of the annealing temperature up to 1000 °C. Nevertheless, in the PL spectra of the films annealed in air at 1000 °C, excitonic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…For example, our previous studies of Mg Zn 1− O thick layers and ceramic specimens prepared from a mixture of oxides using the solidphase reaction method at high temperatures showed that a homogeneous solid solution with the hexagonal structure can be obtained, if the magnesium ox-ide content does not exceed a value of about 20% ( = 0.2). In this case, the band gap increases to 3.7 eV [27,28]. At > 0.2, the additional formation of the MgO phase with cubic structure takes place.…”
Section: Introductionmentioning
confidence: 93%
“…For example, our previous studies of Mg Zn 1− O thick layers and ceramic specimens prepared from a mixture of oxides using the solidphase reaction method at high temperatures showed that a homogeneous solid solution with the hexagonal structure can be obtained, if the magnesium ox-ide content does not exceed a value of about 20% ( = 0.2). In this case, the band gap increases to 3.7 eV [27,28]. At > 0.2, the additional formation of the MgO phase with cubic structure takes place.…”
Section: Introductionmentioning
confidence: 93%
“…In the sample of x = 0.75, a hexagonal phase of the ZnMgO solid solution will be formed instead of ZnO phase. The bandgap of ZnMgO solid solution is larger than that of ZnO, [ 29 ] and, accordingly, the absorption edge of this phase shifts to the short wavelength region.…”
Section: Resultsmentioning
confidence: 99%
“…However, as is well known, ZnO crystallizes and is stabilized in the hexagonal wurtzite lattice, whereas MgO is stabilized in the cubic rock salt lattice. As the Mg content increases, the crystalline structure of ZnMgO ternary alloy will transform through the wurtzite phase (low Mg content), mixed-phase (both hexagonal and cubic phase), and cubic phase (high Mg content) [ 14 , 17 ]. UVPDs based on cubic rock-salt ZnMgO (c-ZnMgO), wurtzite ZnMgO (w-ZnMgO), and mixed-phase ZnMgO (m-ZnMgO) have been reported [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%